CONTEXTUALIZATION OF THE MEANING OF HADITH REGARDING THE EXHORTATION TO INCREASE OFFSPRING FROM THE PERSPECTIVE OF HASAN HANAFI’S HERMENEUTICS: A Counter Effort Against the Childfree Phenomenon - Noorhidayati, Salamah; Ariesti Rasyid, Dara Sri (RIWAYAH, 2023)
This research aims to uncover the meaning of the text and context, as well as the effort to contextualize the meaning of the Hadith concerning the encouragement to have many offspring in order to counter the phenomenon. It poses three research questions: firstly, what is the quality of the Hadith concerning the encouragement to have many offspring. Secondly, we will examine the meaning of the Hadith regarding the encouragement to have many offspring. Thirdly, we will explore the contextualization of the meaning of the Hadith concerning the encouragement to have many offspring within the context of childfree. This study is a literature review with a deductive approach, employing the hermeneutic method of Hadith by Hasan Hanafi through three operational steps, namely historical criticism, eidetic criticism, and practical criticism. As a result of this research, the first finding is that the Hadith about the encouragement to have many offspring is considered to be authentic (sahih lighairihi). Secondly, the textual meaning is the prohibition of celibacy and marrying infertile women, as well as the recommendation to get married, while the contextual meaning is that the Prophet will take pride in having numerous descendants. Thirdly, contextualization of the hadith, which is about having descendants and preserving the lineage.[Penelitian ini dilatar belakangi sejak munculnya fenomena dalam sebuah pernikahan yang mulai marak diperbincangkan. Fenomena tersebut yakni adanya sepasang suami istri yang menolak untuk memiliki anak, karena pada hakikatnya fenomena ini dapat memutuskan mata rantai regenerasi yang mengakibatkan kerusakan dari sisi akidah maupun dari sisi sosial kemasyarakatan. Penelitian ini berusaha untuk mengungkap makna teks dan konteks serta upaya kontekstualisasi makna hadis tentang anjuran memperbanyak keturunan dalam rangka meng-counter fenomena tersebut, dengan mengajukan tiga rumusan masalah yaitu pertama, Bagaimana kualitas hadis tentang anjuran memperbanyak keturunan. Kedua, Bagaimana makna hadis tentang anjuran memperbanyak keturunan. ketiga, Bagaimana kontekstualisasi makna hadis tentang anjuran memperbanyak keturunan dalam konteks childfree. Penelitian ini merupakan jenis studi kepustakaan yang bersifat deduktif dengan menggunakan metode hermeneutika hadis Hasan Hanafi melalui tiga langkah operasional yaitu langkah kritik historis, kritik eidetis, dan kritik praksis. Sebagai hasil temuan dari penelitian ini yaitu pertama, Hadis tentang anjuran memperbanyak keturunan memiliki kualitas shahih lighairihi. Kedua, Makna tekstual yaitu larangan membujang dan menikahi wanita mandul serta anjuran untuk menikah, sedangkan makna kontekstual yakni nabi akan berbangga dengan banyaknya keturunan. Ketiga, Kontekstualisasi makna hadis yakni memiliki keturunan dan menjaaga keturunan.]